Effect of an energy-deficient diet on populations of ciliate protozoans in bovine rumen Efeito da deficiência de energia na dieta sobre a população de protozoários ciliados do rúmen de bovinos - P.C. Soares; I. Martinele; M. D'Agosto; C.A. Maruta; M.C.A. Sucupira; A.C. Antonelli; C.S. Mori; E.L. Ortolani (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2008)
Ten young rumen-cannulated crossbred steers were randomly divided into two groups: a control group (C; n=4), which was fed a balanced diet for daily weight gain of 900g; and a pronounced energy-deprived group (PED; n=6), receiving 30% less of the required energy for maintenance. After 140 days of these alimentary regimes, rumen fluid and urine samples were collected for biochemical and functional tests, before feeding and at 1, 3, 6, and 9 hours after feeding. The energy-deprivation diet caused a significant reduction in the number of Entodinium, Eodinium, Isotricha, Dasytricha, Eremoplastron, Eudiplodinium, Metadinium, Charonina, Ostracodinium, and Epidinium protozoa. There was no effect of the time of sampling in both groups on the total number of ciliates in rumen fluid. A higher number of protozoan forms in binary division were recorded in the control group, at the 6th and 9th hours after feeding (P<0.019). There was a high positive correlation between the total count of protozoans in rumen fluid and glucose fermentation, ammonia, and urinary allantoin excretion index; and a negative correlation between the total count of protozoa and metilene blue reduction, and a medium correlation between the total count of protozoa and total volatile fatty acids concentration. The determination of the protozoa populations does not imply in the use of complex and hard-to-execute techniques, although it is time consuming and needs practice. This exam particularly helps in clinical expected diagnosis. Foram utilizados 10 novilhos mestiços com cânula ruminal, distribuídos em dois grupos: no grupo controle (C; n=4) receberam dieta balanceada para ganho diário de 900g; no grupo tratado com carência pronunciada de energia (CP; n=6), receberam dieta com 30% a menos do nível de mantença em energia. Após 140 dias sob esses regimes de alimentação, foram coletadas amostras do fluido ruminal e urina, para realização de provas bioquímicas e funcionais, antes e às 1, 3, 6 e 9 horas após o fornecimento do alimento. A carência energética resultou em diminuição significativa na quantidade dos protozoários Entodinium, Eodinium, Isotricha, Dasytricha, Eremoplastron, Eudiplodinium, Metadinium, Charonina, Ostracodinium e Epidinium. Não houve efeito da hora de coleta sobre o total de ciliados nos grupos C e CP. Maior número de formas em divisão binária foi registrado no grupo C, na sexta e nona horas pós-alimentação (P<0,019). Observaram-se altas correlações positivas entre a contagem total de protozoários e a fermentação de glicose, amônia e o índice de excreção urinária de alantoína e negativa entre a contagem total de protozoários e a redução do azul de metileno, e correlação média entre a contagem total de protozoários e os ácidos graxos voláteis totais. A determinação da população de protozoários do rúmen é um método simples de avaliação, além de que particularmente auxilia o diagnóstico clínico da função ruminal.